2017
DOI: 10.3389/fphys.2017.00236
|View full text |Cite
|
Sign up to set email alerts
|

Daily Moderate Exercise Is Beneficial and Social Stress Is Detrimental to Disease Pathology in Murine Lupus Nephritis

Abstract: Daily moderate exercise (DME) and stress management are underemphasized in the care of patients with lupus nephritis (LN) due to a poor comprehensive understanding of their potential roles in controlling the inflammatory response. To investigate these effects on murine LN, disease progression was monitored with either DME or social disruption stress (SDR) induction in NZM2410/J mice, which spontaneously develop severe, early-onset LN. SDR of previously established social hierarchies was performed daily for 6 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…To investigate the effect of hAAT on lupus development, we performed hAAT protein and gene therapy treatment in NZM2410 mice, the parental strain of B6.TC mice that spontaneously develops severe early-onset glomerulonephritis from 20 to 40 weeks of age. 36 Female NZM2410 mice were treated with PBS as a control, clinical-grade AAT (2 mg every 3 days) as protein therapy, or rAAV8-CB-hAAT vector (1 × 10 11 vg) as a gene therapy. The treatment started at 8 weeks of age, before the presence of high levels of autoantibodies and clinical disease.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the effect of hAAT on lupus development, we performed hAAT protein and gene therapy treatment in NZM2410 mice, the parental strain of B6.TC mice that spontaneously develops severe early-onset glomerulonephritis from 20 to 40 weeks of age. 36 Female NZM2410 mice were treated with PBS as a control, clinical-grade AAT (2 mg every 3 days) as protein therapy, or rAAV8-CB-hAAT vector (1 × 10 11 vg) as a gene therapy. The treatment started at 8 weeks of age, before the presence of high levels of autoantibodies and clinical disease.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, our previous studies document a diverse array of exacerbated pathologies associated with the persistent induction of Mo production following social stress. For instance, repeated social defeat stress exacerbated lupus nephritis (Aqel et al, 2017) and allergen-induced airway inflammation (Bailey et al, 2009) and promoted the reactivation of latent herpes simplex virus infections (Padgett et al, 1998). Moreover, social defeat stress increased susceptibility to endotoxic shock (Quan et al, 2001), caused increased lung inflammation (Curry et al, 2010), promoted allodynia and hyperalgesia (Sawicki et al, 2018), impaired learning and memory (McKim et al, 2016a), and prolonged anxiety (McKim et al, 2016b, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“… 33 In contrast, daily moderate exercise attenuated systemic inflammation in response to lipopolysaccharide injection in mice. 34 Recently, Aqel, et al 35 demonstrated that daily moderate exercise improves the inflammatory response of LN in NZM2410/J mice through blocking the expression of inflammatory mediators IL-6, tumor necrosis factor-α, CXCL1, and anti-dsDNA antibodies. Their findings also implicated the possibility of adjunct therapeutic strategy for LN.…”
Section: Discussionmentioning
confidence: 99%